Fluorescence screening of collagen preservation in tooth dentine - Czermak, A; Schermelleh, L; Lee-Thorp, J (Elsevier, 2019)
Isotope analysis of collagen from high-resolution sequential samples of dentine has become a popular tool to provide diachronic insights into individual life histories including childhood diet, stress episodes, and mobility during the tooth formation period. New microsampling approaches improve temporal resolution enabling tracking of diet shifts within relatively short time-spans. These methods, however, necessarily deliver small samples and depend upon good collagen preservation at similar high-resolution scales. Yet present methods indicate state of collagen preservation only after sampling and isotope analysis. Here we present a method for prior determination of collagen preservation, based on differential autofluorescence imaging of tooth longitudinal thin sections to map regions of intact and degraded collagen in the corresponding sampling areas. We find that even in dentine areas that were apparently intact based on histology, decay was detected in fluorescence images and that these could be correlated to lower collagen amounts and higher C/N ratios. Areas identified as ‘severely decayed’ dissolved after demineralization. The presented dual-colour autofluorescence imaging approach allows determination of areas of degraded collagen at high resolution. This can be used to detect diagenetic changes in collagen ahead of sampling and facilitates selection of well-preserved samples.